Retail loyalty programs in Malaysia: the relationship of equity, value, satisfaction, trust, and loyalty among cardholders - Omar, Nor Asiah; Alam, Syed Shah; Aziz, Norzalita Abdul; Nazri, Muhamad Azrin (Journal of Business Economics and Management, 2011)
This study examines loyalty programs in Malaysia in terms of perceived equity, value, program satisfaction, program trust, and store loyalty. A total of 400 questionnaires were collected from cardholders in Klang Valley, Malaysia. The hypotheses were based on social exchange and equity theories. The structural equation model that assessed the relationship between the proposed variables was tested using AMOS 6.0. The findings revealed that perceived equity and perceived value of the loyalty program significantly influence program satisfaction and trust. Program trust was the most important predictor of store loyalty. Limitations of the study and recommendations for future research are discussed.Article in English.Mažmeninės prekybos lojalumo programos Malaizijoje: nuosavas kapitalas, vertė, pasitenkinimas, pasitikėjimas ir lojalumasSantrauka. Autoriai analizuoja Malaizijoje paplitusias mažmeninės prekybos programas, t. y. jų vertę, patrauklumą, pasitikėjimą programa ir lojalumą. Tyrime dalyvavo 400 respondentų. Hipotezės buvo pagrįstos socialinių mainų ir lygybės teorijomis. Sudarytas struktūrinis modelis vertina siūlomų rodiklių ir jų variacijų santykinę priklausomybę naudojant AMOS 6.0. Gauti rezultatai parodė, kad tiek nuosavo kapitalo, tiek siūlomos programos lojalumas turi įtakos programos pasitenkinimo ir pasitikėjimo lygiui. Pasitikėjimas programa buvo vienas svarbiausių veiksnių vertinant vartotojų lojalumą.Reikšminiai žodžiai: lojalumo programa, vertė, pasitenkinimas, pasitikėjimas, mažmeninė prekyba, Malaizija.